Investigation of nonlinear wave propagation in water - KOZACZKA, E.; GRELOWSKA, G. (Archives of Acoustics, 1992)
In this paper the effects of nonlinear wave distortion have been described. This problem is characterized for the nonlinear medium. The experimental investigation results of nonlinear propagation have been presented. The wave distortion is connected with the harmonic generation. The measuring set-up used for the investigation of nonlinear wave distortion has been shown. It allows to measure wave distortion by determining harmonic amplitude and their numbers as a function of the distance from a wave source. As a primary wave source, the "sandwich" transducers have been used. The resonance frequencies of these transducers were 30 kHz and 81 kHz respectively. The recorded wave distortions are shown in diagrams and photos. Also the spectrum evolution as a function of distance from the wave source is shown. The investigation results are connected with the weak nonlinear wave distortion.